1981
DOI: 10.1115/1.3230791
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Centrifugal Impeller and Diffuser Flow

Abstract: The flow field development within a centrifugal compressor stage was analyzed using an advanced laser velocimetry [4]. A splitter blade impeller coupled with a vaned and vaneless diffuser has been found to have similar internal flow patterns for both the vaneless and vaned diffuser design. Different velocity profiles have been analyzed for adjacent channels behind the splitter blade leading edge. A considerable wake flow was observed near the impeller exit. Detailed optical measurements within the vaned diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 0 publications
3
57
0
2
Order By: Relevance
“…The first reported measurements were obtained by Eckardt (1976) using a Laser-2-Focus Velocimeter. Since then, several other researchers ( Adler and Levy, 1979;Eckardt, 1979;Krain, 1981Krain, , 1987Ahmed and Elder, 1990;Pak et al, 1993;Krain et al, 1995) have used laser anemometers to measure the flow fields within high-speed centrifugal impellers configured with both vaned and vaneless diffusers. Hathaway et al (1993) reported results from a study in a large low-speed compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The first reported measurements were obtained by Eckardt (1976) using a Laser-2-Focus Velocimeter. Since then, several other researchers ( Adler and Levy, 1979;Eckardt, 1979;Krain, 1981Krain, , 1987Ahmed and Elder, 1990;Pak et al, 1993;Krain et al, 1995) have used laser anemometers to measure the flow fields within high-speed centrifugal impellers configured with both vaned and vaneless diffusers. Hathaway et al (1993) reported results from a study in a large low-speed compressor.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is no definitive resolution of whether the existence and location of large regions of throughflow velocity deficit adversely impact loss generation within the impeller. Detailed measurements of the internal flow made by Krain [5], Hathaway et al [6], and more recently Skoch et al [7] are helping to fill some gaps. Moreover, application of CFD moored to these benchmark data sets can greatly increase the information content and also enhance our ability to make design choices.…”
Section: Introduction Introductionmentioning
confidence: 99%
“…Currently, grids used in the numerical calculation can be divided into two categories, including structured and unstructured grids. In view of the complex geometry of the outdoor air conditioner, unstructured grids is selected as adaptability grid type to the geometry structure which can adapt with the irregularly changing fan blade shape fitly [2] . So the model can be divided into air inlet domain, the impeller domain and export domain.…”
Section: Geometric Model and Mesh Generationmentioning
confidence: 99%